A robust predictive current controller for healthy and open-circuit faulty conditions of five-phase BLDC drives applicable for wind generators and electric vehicles. (1st March 2015) - Salehi Arashloo, Ramin; Salehifar, Mehdi; Romeral, Luis; Sala, Vicent
Highlights: Model predictive deadbeat control of generator stator phase currents. Fault tolerant control of five-phase BLDC generator. Control of stator phase currents under normal and open-circuit faulty conditions. MATLAB simulation and experimental verification of proposed control method. Verification of robustness and fast respond of proposed controlling method. Abstract: Fault tolerant control of five-phase brushless direct current (BLDC) machines is gaining more importance in high-safety applications such as offshore wind generators and automotive industries. In many applications, traditional controllers (such as PI controllers) are used to control the stator currents under faulty conditions. These controllers have good performance with dc signals. However, in the case of missing one or two of the phases, appropriate reference currents of these machines have oscillatory dynamics both in phase- and synchronous-reference frames. Non-constant nature of these reference values requires the implication of fast current controllers. In this paper, model predictive deadbeat controllers are proposed to control the stator currents of five-phase BLDC machines under normal and faulty conditions. Open circuit fault is considered for both one and two stator phases, and the behaviour of proposed controlling method is evaluated. This evaluation is generally focused on first, sensitivity of proposed controlling method and second, its speed in following reference current values under transient states. Proposed method is simulated and is verified experimentally on a five-phase BLDC drive.